Revisión taxonómica del género Sphagnum L. Sección Cuspidata (Musci, Sphagnaceae) en la Península Ibérica - Munín, Estrella; Fuertes, Esther (Lazaroa, 2001)
The revision of specimens of Sphagnum L. Cuspidata (Lindb.) Schlieph. from Herbaria in France and Spain (PC) is presented. Eight taxa are confirmed for Spanish moss flora: S. angustifolium, S. brevifolium, S. cuspidatum, S. fallax, S. flexuosum, S. majus subsp. norvergicum, S. tenellum, S. viride; three for Portuguese moss flora: S. cuspidatum, S. flexuosum and S. tenellum and one for Andorra: S. fallax. S. pulchrum (Lindb.) Warnst var. virescens Warnst. fo. gracilescens is excluded from the Spanish moss flora. All taxa grow in wet oligotrophic soils with a humid-hyperhumid ombroclimate (annual average precipitation exceeds 1000 mm) that is favourable for their growth, and they are distributed exclusively in the northern half of the Iberian Peninsula, their presence slowly diminishing from North to South and from West to East of the Peninsula in parallel with a decrease in mean annual precipitation and increased summer dryness. The most common taxa in deciduous forests and mountainous areas (montane and supra-Mediterranean belt) are S. tenellum, S. flexuosum and S. fallax throughout the Cantabrian Mountains, Pyrenees, northern Iberian System and Central System. S. cuspidatum, S. viride and S. brevifolium, which are absent from the Pyrenees, are common in the areas with greatest oceanic influence (coline-montane belt) in the mountains of the N-NW of the Peninsula. Serra da Estrela (Portugal) is currently the southernmost locality on the Iberian Peninsula for S. cuspidatum. The most uncommon taxa are S. angustifolium and S. majus subsp. norvergicum, which occur in mountainous areas with a continental climate at 1500-2000 m (supramontane-subalpine belt). S. majus subsp. norvergicum is only represented at three Spanish sites (two in the Cantabrian Mountains and one in the La Demanda Massif). A key and SEM microphotographs for morphological and anatomical characters of some of the taxa studied are given.